Consumer's perception on Disney licensed character apparel brands for children's wear in selected malls in Metro Manila in relation to visual branding - Yu, Jaymee Cyrene De Jesus (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This research aimed to know the consumers? perception on certain children?s wear character apparel brands in selected outlets in Metro Manila. Specifically, the research determined which character is most popular and how color, price, and apparel category affected the consumers? considerations in patronizing these brands, and established if the forecasted look of each character as planned by the licensors match the consumers? perceived image or ?defining characteristic? of the specific character brand. The researcher focused on the Disney character apparel brands that were available in the Department Stores specifically in the girl?s children?s wear section. The research used a descriptive survey approach on consumers, particularly mothers, in the act of purchasing Disney character apparel on selected malls in Metro Manila. Stratified random sampling was used, therefore, respondents of the survey to be qualified would actually have to be in the selling area, browsing through the products, or actually purchasing the items. A total of Four Hundred (400) respondents were given survey questionnaires from eight (8) different malls selected randomly and at different time intervals. The instruments used were the survey questionnaires and the interviews which formulated the follow-up questions in case answers to the questionnaire had discrepancies. The data gathered were then collated, treated and analyzed statistically and are presented through charts and graphs to show the trends of the respondents? answers. Based on the findings of the study, Disney Princess, turned out to be the most liked among the Disney characters. The survey also showed that mothers and their children share their favorite character. Therefore consumers tend to purchase and patronize the character apparel brand of their preferred character. This finding on the popularity of Disney Princes was well supported by the other findings of the survey on color, price, apparel category, and image. Pink and blue, as the most favored color combination, the dress, as the most preferred apparel category, and ?pretty and cute?, as the most popular defining characteristics, are specifically assigned imaging attributes of the Disney Princess character. The respondents also gave a high rating on this character brand in terms of affordability. The results suggest that Disney Princess has an advantage among the four Disney character apparel brands since it caters to the needs and wants of the consumers. The research was also able to conclude that the selected consumers? preferences match those of the forecasts of the licensors for the character apparel brand Disney Princess.